1990
DOI: 10.1001/jama.264.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fatigue. A prospective clinical and virologic study

Abstract: To evaluate the clinical and virologic course of patients with chronic fatigue who had elevated Epstein-Barr virus (EBV) titers, we prospectively followed up 26 patients with serial cultures for EBV in blood and saliva and serial EBV serologic and clinical and psychiatric evaluations, and we compared these results with those for healthy controls. The frequency of isolating EBV in blood or demonstrating EBV infection by in situ hybridization in blood lymphocytes or in saliva was similar in patients and controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
5

Year Published

1991
1991
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(41 citation statements)
references
References 37 publications
2
33
1
5
Order By: Relevance
“…However, this is unlikely to reflect the real situation due to the small number of subjects reporting alternative trigger factors. Despite a number of publications showing that viral infections only explain a small proportion of CFS cases (Gold et al, 1990;Heneine et al, 1994;Mawle et al, 1995), we found that the proportion of patients reporting viral infection as a trigger factor (76%) was high. This suggested a possible relationship between carnitine deficiency and infections (Mintz, 1995;Famularo et al, 2004).…”
Section: Discussioncontrasting
confidence: 96%
“…However, this is unlikely to reflect the real situation due to the small number of subjects reporting alternative trigger factors. Despite a number of publications showing that viral infections only explain a small proportion of CFS cases (Gold et al, 1990;Heneine et al, 1994;Mawle et al, 1995), we found that the proportion of patients reporting viral infection as a trigger factor (76%) was high. This suggested a possible relationship between carnitine deficiency and infections (Mintz, 1995;Famularo et al, 2004).…”
Section: Discussioncontrasting
confidence: 96%
“…Gold et al (20) did not find any difference in the HHV-6 titres between their patients and controls. This may be explained by the fact that only six of their 26 patients fulfilled the CDC criteria: most of their patients were probably similar to group B of the present study.…”
Section: Discussionmentioning
confidence: 73%
“…Segundo Wessely (1989), a história da síndrome da fadiga crônica começou com a publicação, no início dos anos 80, de algumas séries de casos que descreviam uma doença com sintomas semelhantes aos efeitos retardados de uma infecção viral, manifestada por fadiga e outros sintomas, em grande parte subjetivos e aparentemente associados a evidências serológicas de infecções prolongadas pelo vírus Epstein-Barr (EB) -muito embora alguns estudos, como o de Gold et al (1990), não tenham demonstrado correlação entre parâmetros serológicos da atividade desse vírus e a condição clínica em questão.…”
Section: Contexto De Emergência Das Síndromes Funcionaisunclassified